A emergência da disciplinarização da libras em tempos de inclusão - Rodrigues, Jane Teresinha Donini (2015)
The object of this thesis is the study of the imminence of the Brazilian Sign Language as subject into the historic processes that constitute the educational and political scenarios of the contemporary Brazil. I carry out the task to look at the official documented discourses produced in the scenarios of the National Congress and in governmental bodies, between 1996 and 2005, time at which there was a proposition to turn official the Brazilian Sign Languages and the definition about its inclusion in the curriculum as subject. For this purpose, I decided on three legal documents as research material – the Bill Nº 131 of the Federal Senate of 1996 (PLS 131/1996), the Bill Nº 10.436/2002 and the decree Nº 5626/2005. However, the analysis focus falls especially on various records such as legislative minutes, reports, views, technical notes and other referrals that had their publications around this time, because the central interest was not on what was stated on the laws, but on what was specified so they could get constituted. In this sense, the objective was to look into the happenings that preceded the entry of Brazilian Sign Language in the curricular field, and to understand the regimes of truths that were selfmobilizing, the power games that went attaching distinct meanings to the discourses produced during the time in which the standardization of the Brazilian Sign Language was in operation. For such assignment, I sought inspiration theoretical-methodological in the field of Foucauldian studies, using the analysis discourse as a tool and taking the standard notions, standardization and uniformity as lenses to look at the process of disciplinarization of Brazilian Sign Language within the centre of Brazilian political decisions. In this development, I aimed to locate the theme investigated presently, immersed in a society project from which the inclusion became an imperative of state- building, understanding that their effects have higher proportions when incorporated to the discourse of laws, becoming more powerful to operate as truth in the circuit of what we can call the engines of the actual society – the economy and education. Furthermore, the links between the theme of the research and the historic processes were productive. These enable the comprehension of the disciplinary constitution of knowledge, the current forms of organization of knowledge and the relationship with the production of conditions to the merging of Brazilian Sign Language in the curricula and, in this instance, in the curriculum, as it maximised certain practices in the contemporaneity that operate in the deaf standardization. In this way, it was possible to comprehend that the effects and transformation resulting from this process are not located in the cold letter of the law, but beyond it, in the vast standard scope that it produces. The standard is established as measure, benchmark and reference, it is what operates as a fluid that spread out in the population, it penetrates each individual’s interiority and it is distributed in spaces, in times, in its own existence.